A study on the choice of library for career practice by U.P. Bachelor of Library Science graduates from school year 1993-1995 - Lucero, Dante Winston S. (1997)
This thesis aims to study the factors which influenced the Bachelor of Library Science graduates of the University of the Philippines Institute of Library Science for the school years 1993, 1994, and 1995 in their decision to transfer to another type of library in practicing their careers in librarianship. The objectives of the study are to find out what type of library the UP BLS graduates are working at present, why they chose such type of library for their career practice; to determine how many libraries have they worked before and what type of libraries were they; and to